Pengaruh koneksi politik dan biaya terhadap knerja perusahaan sektor Pertambangan - Soemaryono, Soemaryono; Ismangil , Ismangil (Jurnal Audit dan Perpajakan (JAP), 2022)
The aim of this research is to empirically examine the influence of political connection factors and political cost factors on the performance of companies in the mining sub-sector. The population used in this study are mining sub-sector companies listed on the Indonesia Stock Exchange in 2018-2020 with a total sample of 23 companies. The independent variables of this study are political connections and political costs, while the dependent variable is company performance which is measured by using Return on Assets (ROA). The analysis method uses multiple linear regression and the analysis model uses the t test. The results of the hypothesis test show that political connections have an influence on the performance of the mining sub-sector, while political costs have no effect on the performance of the mining sub-sector.